Implementation of the Sustainability Reporting Standard Based on Sustainability Disclosure Standards 1 and 2 for PT XYZ - Darjito Wahyu Probo Apsoro; Asep Darmansyah (Green Publisher Indonesia, 2026)
This study analyzes the readiness of PT XYZ to implement the Sustainability Disclosure Standards (PSPK) 1 and 2, which will become mandatory in Indonesia starting in 2027. Although the company has used the GRI Standards and POJK 51 as the basis for its sustainability reporting, its current disclosures have not fully met PSPK requirements, particularly in linking sustainability issues to financial performance, assessing climate-related risks, and integrating sustainability into strategic decision-making. Using a qualitative approach, the research employs SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in PT XYZ's existing sustainability report, followed by Actor–Network Theory (ANT) to map the interactions among human and non-human factors influencing PSPK implementation. Data were collected through document analysis, interviews with internal stakeholders, and a review of relevant standards. The findings indicate that PT XYZ has a strong foundation for the transition, supported by its current reporting structure and governance practices; however, notable gaps exist in materiality assessment, risk quantification, climate governance, data integration, and system readiness. The ANT analysis further reveals the need for coordinated internal regulation, enhanced cross-unit collaboration, strengthened data systems, and capacity-building to support accurate and consistent sustainability disclosures. This study concludes that, with structured preparation and alignment of actors, PT XYZ can successfully adopt PSPK 1 and 2 and enhance the credibility, comparability, and strategic relevance of its sustainability reporting.